Shopping to save: green consumerism and the struggle for northern Maine - Harrison, Blake (Cultural Geographies, 2006)
Between 2001 and 2003, Roxanne Quimby - then the sole owner of a natural personal-care products company named Burt's Bees - invested millions of dollars of her company's profits in tens of thousands of acres of forestland in northern Maine. Her intention was to donate that land to the United States government on behalf of a controversial national park proposed for the region - the Maine Woods National Park. Quimby's actions set off sharp debates between policy makers, environmentalists and residents of northern Maine. As this article suggests, those debates were informed in part by their association with green consumerism. When consumers purchase `environmentally friendly' products like those made by Burt's Bees, they typically envision their actions as having positive consequences for places associated directly with the production and consumption of that product. In this case, however, profits from a green consumer product were reinvested outside its immediate commodity chain, thereby implicating green-consumer decisions in a politics of identity and landscape control beyond that product's lifecycle. This paper explores that process, suggesting that even the most well-intended consumer choices can carry social and environmental consequences into new and perhaps unexpected terrain. When we shop to save, we can never be quite certain of what it is that we are saving.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/167-946-655-886-089 tex.type: [object Object]
Keywords: Apoidea; Maine; North America; United States; consumption behavior; dept.egm; profitability

Offshore threats: Liquefied natural gas, terrorism, and environmental debate in Connecticut - Harrison, Blake (Annals of The Association of American Geographers, 2008)
Broadwater Energy is one of a number of recent proposals to construct a liquefied natural gas facility along the East Coast of the United States. The proposal calls for the construction of an import and regasification terminal in Long Island Sound, roughly halfway between the states of New York and Connecticut. First made public in 2004 by its sponsors, TransCanada and Shell, the Broadwater proposal has inspired opposition from a range of interest groups. An examination of the Broadwater debate with a focus on arguments made by Connecticut residents in the months leading up to the release in late 2006 of the proposal's Draft Environmental Impact Statement reveals explicit and implicit points of overlap between concerns about the facility's environmental impacts and concerns about its status as a potential terrorist target. Discussions about terrorism deployed in the Broadwater debate have initiated and informed a politics of scale through which themes common to environmental debates have been transformed. This transformation, in turn, highlights the discursive and material influence of terrorism in contemporary U.S. society. Concerns about terrorist attacks have been deployed by activists to enhance the strength of an otherwise environmental debate and, in the process, those concerns have developed the potential to shape land use policy in Long Island Sound. Key Words: environmentalism, liquefied natural gas, Long Island Sound, scale, terrorism.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/056-913-849-043-885 tex.unique-id: [object Object]
Keywords: Connecticut; Environmentalism; Liquefied natural gas; Long Island Sound; North America; Scale; Terrorism; United States; container terminal; dept.egm; environmental impact; environmental policy; environmentalism; land use planning; liquefied natural gas; offshore engineering; terrorism